Setting the minimum utility gas flowrate targets using cascade analysis technique - Chwan, Dominic Yee Foo; Abdul Manan, Zainuddin (American Chemical Society, 2006)
This work describes the gas cascade analysis (GCA) as an extension to cascade analysis technique for targeting the minimum flowrates for water and property-based networks. The GCA technique enables quick and accurate identification of the minimum flowrate targets, pinch-point location(s), and resource allocation targets for a utility gas network. Multiple-pinch problems and appropriate selection of gas purification techniques were systematically assessed via the GCA. The GCA technique was successfully used to determine the minimum flowrate targets for nitrogen, oxygen, and hydrogen utility gas networks prior to detailed design.